Synthesis, identification and application of a new ionic liquid based on 1-vinylimidazole, immobilized on graphene oxide nanosheets - Masoumeh Mirhasani; Reza Sandaroos; Behrooz Maleki; Sahar Peiman (Case Studies in Chemical and Environmental Engineering)
In this research, a novel catalyst GO@[PBVIm]HSO4, which is an acidic polymer ionic liquid supported on a graphene oxide substrate, was synthesized. First, (3-aminopropyl) triethoxysilane was attached as a linker to the prepared graphene oxide. In the next step, 1-butyl vinyl imidazolium bromide was used to synthesize the expected polymer catalyst on a solid support. The efficiency of this catalyst was used in various organic chemical reactions such as the synthesis of chromene, xanthene, and dihydropyrimidinone derivatives. Short reaction time, suitable temperature, excellent yield of products, and very good activity of recycled catalyst are among the advantages of this heterogeneous catalyst synthesis.